A prospective clinical trial evaluating changes in the wound microenvironment in patients with chronic venous leg ulcers treated with a hypothermically stored amniotic membrane. Issue 1 (6th May 2021) - McQuilling, John P.; Carter, Marissa J.; Fulton, Judith A.; Patel, Keyur; Doner, Bryan; Serena, Thomas E.; Mowry, Katie C.
Abstract: Amniotic tissues have been long utilised to treat chronic wounds; however, there are few studies evaluating how the wound microenvironment responds to these therapies. The goal of this study was to evaluate the changes in wounds treated with a hypothermically stored amniotic membrane (HSAM). In this prospective single‐arm study, 15 female patients with venous leg ulcers were treated with HSAM from male donors and standard of care for 12 weeks. Over the course of the study, wound exudate was collected and evaluated using proteomic microarrays. Biopsies were collected during the course of treatment to detect the presence of HSAM tissue. By 4 weeks, 60% of subjects achieved 50% or greater reduction in wound size, and by 12 weeks, 53% of subjects achieved 100% re‐epithelialization. HSAM DNA was detected in 20% of biopsies as determined by the detection TSPY4, indicating HSAM was no longer present within the wound bed approximately 7 days from the last treatment for the majority of wounds. Proteomic analysis of wound exudate found that wounds on a healing trajectory had significantly higher levels of MMP‐10, MMP‐7, and TIMP‐4 and significantly lower levels of CX3CL1, FLT‐3 L, IL‐1ra, IL‐1a, IL‐9, IL‐2, IL‐3, MCP‐1, and TNF‐b compared with other wounds.